2001
DOI: 10.1149/1.1397772
|View full text |Cite
|
Sign up to set email alerts
|

LiCoO[sub 2] Cathode Material That Does Not Show a Phase Transition from Hexagonal to Monoclinic Phase

Abstract: Structural instability of LiCoO2 can be improved by sol-gel coating of Al2O3 and subsequent heat-treatments. While Al2O3 phase does not exist after heat-treatments, solid solution LiCo1−xAlxO2 that has discretely higher Al concentration was formed at the surface up to ∼500 Å inside the particle. However, heat-treatment to 700°C results in the presence of the solid solution beyond ∼500 Å. The different Al concentration at the surface significantly affects the structural stability of the materials during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
151
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(157 citation statements)
references
References 13 publications
6
151
0
Order By: Relevance
“…However, the origin responsible for the increased performance is not well understood. Understanding the mechanism responsible for the enhancement in cycling stability provided by the coatings/surface modification is essential to further stabilize positive electrode materials for applications that demand high cycle life such as electrical vehicles and stationary storage.Enhanced performance in cycling associated with surface coating has been attributed to phase transitions, 3,4,[12][13][14][15] The recent investigation by Dahèron et al,18 showed that the substitution of Al for Co not only increases the ionic nature of the Co-O bond through orbital mixing, but also that the substitution reduces the basicity of the LiCoO 2 surface, thus making the surface less receptive or vulnerable to acidic attack in the electrolyte. However, this benefit can be temporary as recent work indicates that the Li-Al-Co-O surface region is consumed during cycling.…”
mentioning
confidence: 99%
“…However, the origin responsible for the increased performance is not well understood. Understanding the mechanism responsible for the enhancement in cycling stability provided by the coatings/surface modification is essential to further stabilize positive electrode materials for applications that demand high cycle life such as electrical vehicles and stationary storage.Enhanced performance in cycling associated with surface coating has been attributed to phase transitions, 3,4,[12][13][14][15] The recent investigation by Dahèron et al,18 showed that the substitution of Al for Co not only increases the ionic nature of the Co-O bond through orbital mixing, but also that the substitution reduces the basicity of the LiCoO 2 surface, thus making the surface less receptive or vulnerable to acidic attack in the electrolyte. However, this benefit can be temporary as recent work indicates that the Li-Al-Co-O surface region is consumed during cycling.…”
mentioning
confidence: 99%
“…It was shown by many that the cycle life of LiCoO 2 at higher voltages (i.e., >4.2 V) can be improved by metal oxide coatings such as Al 2 O 3 , SnO 2 , ZrO 2 , TiO 2 , MgO, [34,[38][39][40][41][42], metal phosphate coatings such as AlPO 4 [43][44][45][46], metal fluoride coatings such as AlF 3 and LaF 3 [47,48] and multicomponent metal fluoride coatings such as aluminum-tungsten-fluoride (AlW x F y ) [49]. Although the underlying reasons for such an improvement in cycle life of LiCoO 2 at higher cut-off voltages due to coatings are still debatable [35,50,51], following mechanisms have been suggested: coating (i) inhibits the structural transformation [34,52], (ii) acts as a physical barrier, Figure 9, between the electrolyte and the active material, and prevents the trace amounts of hydrogen fluoride (HF) and water present in the electrolyte from reaching the active material thus effectively suppresses cobalt dissolution and the associated oxygen evolution [53,54], (iii) converts Lewis acids which in return corrode the insulating surface species and improves the electronic conductivity of the solid electrolyte interface (SEI) layer on LiCoO 2 [50]. Appl.…”
Section: Cathodementioning
confidence: 99%
“…The realized capacity of the LiCoO 2 based electrode may be increased by charging beyond 4.2 V, but must also avoid the associated structural change that occurs at higher voltages. This has been achieved by encapsulating LiCoO 2 particles with stable ceramic compounds such as TiO 2 , Al 2 O 3 , and ZrO 2 [4][5][6][7][8], and by novel surface modification techniques [4]. An additional advantage of this technique is related to a "barrier effect" that occurs by the formation of an outer shell, which shields the active LiCoO 2 core from the electrolyte and inhibits detrimental side reactions.…”
Section: Introductionmentioning
confidence: 99%